Gambaran Pengetahuan Pertolongan Pertama Masyarakat Pada Korban Kecelakaan Lalu Lintas - Hidayat, Adi Firman; Nirmalasari, Novita (Jurnal Kesehatan, 2023)
Traffic accidents are a public health problem. Actions for handling accident victims are greatly influenced by individual knowledge about first aid for accident victims to reduce the number of disabilities and deaths. The aim of this research is find out the level of public knowledge about first aid for traffic accident victims in, Patalan, Jetis, Bantul, Yogyakarta. The research was descriptive research with a cross-sectional approach. The sample consisted of 91 respondents used purposive sampling. Data was collected using a questionnaire sheet on the level of public knowledge regarding first aid in traffic accidents. Analysis used univariate analysis. The results of this research showed that the majority were male (54.9%), aged 45-55 (45.1%), had a high school/vocational school education level (54.9%), had been exposed to sources of information (82, 4%), received information from counseling (56.0%), and had never helped traffic accident victims (83.5%). An overview of the level of public knowledge regarding first aid for traffic accident victims found that the majority had a group of knowledge in the excellent category (89.0%). Community knowledge in Padukuhan Patalan, Jetis, Bantul regarding first aid for traffic accidents is in the excellent category.   Keywords: first aid, knowledge, traffic accident